Regulation of the Germinal Center Response - Stebegg, Marisa; Kumar, Saumya D.; Silva-Cayetano, Alyssa; Fonseca, Valter R.; Linterman, Michelle A.; Graca, Luis (Frontiers in Immunology, 2018)
The germinal centre (GC) is an organized microstructure that forms in lymphoid tissues that produces long-lived antibody secreting plasma cells and memory B cells, which can provide protection against reinfection. Within the GC, B cells undergo somatic mutation of the genes encoding their B cell receptors, which following successful selection can lead to the emergence of B cell clones that bind antigen with high affinity. However, this mutation process can also be dangerous, as it can create autoreactive clones that can cause autoimmunity. Because of this, regulation of GC reactions is critical to ensure high affinity antibody production and to enforce self-tolerance by avoiding emergence of autoreactive B cell clones. A productive GC response requires the collaboration of multiple cell types: The stromal cell network which orchestrates GC cell dynamics by controlling antigen deliver and cell trafficking. T follicular helper (Tfh) cells which are unique in providing specialized help to GC B cells through cognate T-B cell interactions, and Foxp3+ T follicular regulatory (Tfr) cells are key mediators of GC regulation. However, regulation of GC responses is not a simple outcome of Tfh/Tfr balance, but also involves the contribution of other cell types to modulate the GC microenvironment and to avoid autoimmunity. Thus, the regulation of the GC is complex, and occurs at multiple levels. In this review we outline recent developments in the biology of cell subsets involved in the regulation of GC reactions, in both secondary lymphoid tissues and tertiary lymphoid structures. We discuss the mechanisms which enable the generation of potent protective humoral immunity whilst GC-derived autoimmunity is avoided.